The potential of task-shifting in scaling up services for prevention of mother-to-child transmission of HIV: a time and motion study in Dar es Salaam, Tanzania - Helga Naburi; Anna Mia Ekström; Phares Mujinja; Charles Kilewo; Karim Manji; Gunnel Biberfeld; David Sando; Guerino Chalamila; Till Bärnighausen (BMC, 2017)
Abstract Background In many African countries, prevention of mother-to-child transmission of HIV (PMTCT) services are predominantly delivered by nurses. Although task-shifting is not yet well established, community health workers (CHWs) are often informally used as part of PMTCT delivery. According to the 2008 World Health Organization (WHO) Task-shifting Guidelines, many PMTCT tasks can be shifted from nurses to CHWs. Methods The aim of this time and motion study in Dar es Salaam, Tanzania, was to estimate the potential of task-shifting in PMTCT service delivery to reduce nurses' workload and health system costs. The time used by nurses to accomplish PMTCT activities during antenatal care (ANC) and postnatal care (PNC) visits was measured. These data were then used to estimate the costs that could be saved by shifting tasks from nurses to CHWs in the Tanzanian public-sector health system. Results A total of 1121 PMTCT-related tasks carried out by nurses involving 179 patients at ANC and PNC visits were observed at 26 health facilities. The average time of the first ANC visit was the longest, 54 (95% confidence interval (CI) 42-65) min, followed by the first PNC visit which took 29 (95% CI 26-32) minutes on average. ANC and PNC follow-up visits were substantially shorter, 15 (95% CI 14-17) and 13 (95% CI 11-16) minutes, respectively. During both the first and the follow-up ANC visits, 94% of nurses' time could be shifted to CHWs, while 84% spent on the first PNC visit and 100% of the time spent on the follow-up PNC visit could be task-shifted. Depending on CHW salary estimates, the cost savings due to task-shifting in PMTCT ranged from US$ 1.3 to 2.0 (first ANC visit), US$ 0.4 to 0.6 (ANC follow-up visit), US$ 0.7 to 1.0 (first PNC visit), and US$ 0.4 to 0.5 (PNC follow-up visit). Conclusions Nurses working in PMTCT spend large proportions of their time on tasks that could be shifted to CHWs. Such task-shifting could allow nurses to spend more time on specialized PMTCT tasks and can substantially reduce the average cost per PMTCT patient.